The Effect of Company Growth and Inflation on Company Valuation - Sunjaya, Robi; Munandar, Agus (Newinera Publisher, 2025)
The purpose of this research is to examine how corporate expansion and inflation affect the worth of companies in the resort, cruise, and hospitality industries that are listed on the Indonesia Stock Exchange (IDX). The study makes use of secondary data that was obtained from these firms' 2018–2022 annual financial reports. By employing a purposive sampling technique, 15 companies were selected, resulting in 75 observations aligned with the study's objectives. Panel data analysis techniques were used to examine the data. The results show that although inflation has a positive and considerable impact on company value, sales growth has no discernible effect. Second, the joint effect of sales growth and inflation accounts for most of the observed value growth in firms. This has important implications for company management, as they need to leverage firm value for competitive advantages in rapidly changing market conditions.